OSS System Innovation 'Si Peri Jempol Boss' for ‘UMKM’ in Kulon Progo Regency in 2019-2020 - Yanti, Rizki; Aji , Juhari (Proceedings of Universitas Muhammadiyah Yogyakarta Graduate Conference, 2022)
This research aims to explain Licensing System Innovation Online Single Submission ‘Si Peri Jempol BOSS’ for Micro, Small and Medium Enterprises in Kulon Progo Regency in 2019-2020. The policy of Government Regulation Number 24 of 2018 concerning Integrated Electronic Business Licensing Services or Online Single Submission (OSS), regulates every local government to carry out reforms in the implementation of business licensing services through OSS. The Kulon Progo Regency Government through the Investment and Integrated Services Agency (DPMPT) presents the Si Peri Jempol BOSS’s innovation as a form of embodiment of this policy and as an answer to the problems of business licensing services for Micro, Small and Medium Enterprises (MSMEs) in Kulon Regency. Progo. The research method used is a qualitative method with a case or field study approach. Data collection techniques were carried out through documentation and interviews. The data analysis used refers to the operational definition using the MEPIN (Measuring Public Innovation in Nordic Country) theory in which there are three indicators of public service innovation, namely Input, Process and Impact. The results of the study indicate that there are input in this Si Peri Jempol BOSS’s innovation, seen from the human resources involved and the infrastructure used. Si Peri Jempol BOSS's innovation also shows process indicators, because in the implementation of this innovation there are procedures and processes that are followed, and there are factors that support and hinder the implementation of this innovation. Si Peri Jempol BOSS's innovation shows an impact, because of the impact resulting from this innovation.